Genotype-by-environment interactions for starch, mineral, and agronomic traits in pearl millet hybrids evaluated across five locations in West Africa - Gangashetty, Prakash I.; Yadav, Chandra Bhan; Riyazaddin, Mohammed; Vermula, Anilkumar; Asungre, Peter Anabire; Angarawai, Ignatitius; Mur, Luis A. J.; Yadav, Rattan S. (Frontiers in Plant Science, 2023)
Introduction Pearl millet is a staple cereal grown in the harshest environments of arid and semi-arid regions of Asia and sub-Saharan Africa. It is the primary source of calories for millions of people in these regions because it has better adaptation to harsh environmental conditions and better nutritional traits than many other cereals. By screening the pearl millet inbred germplasm association panel (PMiGAP), we earlier reported the best genotypes with the highest concentration of slowly digestible and resistant starch in their grains. Methods In the current study, we tested these 20 top-performing pearl millet hybrids, identified based on starch data, in a randomised block design with three replications at five locations in West Africa, viz. Sadore and Konni (Niger), Bambey (Senegal), Kano (Nigeria), and Bawku (Ghana). Phenotypic variability was assessed for agronomic traits and mineral traits (Fe and Zn). Results and discussion Analysis of variance demonstrated significant genotypic, environmental, and GEI effects among five testing environments for agronomic traits (days to 50% flowering, panicle length, and grain yield), starch traits (rapidly digestible starch, slowly digestible starch, resistant starch, and total starch), and mineral trait (iron and zinc). Starch traits, such as rapidly digestible starch (RDS) and slowly digestible starch (SDS), showed nonsignificant genotypic and environmental interactions but high heritability, indicating the lower environmental influence on these traits in the genotype × testing environments. Genotype stability and mean performance across all the traits were estimated by calculating the multi-trait stability index (MTSI), which showed that genotypes G3 (ICMX207070), G8 (ICMX207160), and G13 (ICMX207184) were the best performing and most stable among the five test environments.